Exploring Multifactorial Expressed Emotion among Caregivers of Bipolar Disorder Patients: Insights from a Pilot Study in Tamil Nadu, India - Vrinda Sankar Kala; Arul Saravanan Ramachandran; Manesh Muraleedharan; Alaka Omprakash Chandak; Girija Mahale (Indian Journal of Social Psychiatry)
Background: Expressed emotion (EE) among caregivers of bipolar mood disorder patients has been identified as a risk factor for relapse. Objective: This study aims to understand various underlying reasons related to EE in caregivers of bipolar mood disorder. Methodology: This study was conducted in Tamil Nadu, India, using a constructivist grounded theory method to study this phenomenon. Results: Study findings suggest the multifactorial nature of the EEs of caregivers. Sociocultural factors, healthcare-related issues, and patient care-related stress led to caregiver burden and EE, which can be reflected in patient care. Conclusion: Caregivers’ EE is linked to various sociocultural and financial issues and healthcare-related issues such as the cost of treatment and the availability and inaccessibility of treatment. Furthermore, it is essential to note that many caregivers reported high levels of various components of EE.